Analisis Penerapan Hygiene dan Sanitasi pada Penyelenggaraan Makanan Karyawan di Pangeran Beach Hotel Padang - Septia Dwi Astuti; Kasmita Kasmita (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This research starts from observations about hygiene and sanitation with the background of the problems that arise are employees who do not use aprons and gloves, pay less attention to the cleanliness of eating and drinking utensils, unclean eating places. This study aims to analyze the application of hygiene and sanitation at Pangeran Beach Hotel Padang which includes 3 indicators, namely: Personal Hygiene, Equipment, and Dining Area. This type of research is descriptive research with quantitative and qualitative data. Data collection techniques with an observation guide prepared using a guttman scale, documentation and interviews. Determination of informants with Purposive Sampling Technique in this study was determined as many as 10 people. Quantitative data analysis techniques are assisted by Microsoft excel, qualitative data analysis techniques, namely reduction, presentation of data and conclusions.